Diseñar una propuesta de plan de gestión administrativo y financiero para el establecimiento de comercio Nitro Motos en Cali (2020)
The realization of this work is in order to apply the knowledge acquired throughout the career of Business Administration at the University Antonio Nariño, in an administrative and financial analysis, to generate a plan of administrative and financial management for the marketer of motorcycle parts Nitro Motorcycles in the city of Cali.